An in vitro comparison of three nucleus pulposus removal techniques for partial intervertebral disc replacement: An ultra‐high resolution MRI study - Tamanna Rahman; Nicoleta Baxan; Robert T. Murray; Saman Tavana; Thomas P. Schaer; Nigel Smith; Jonathan Bull; Nicolas Newell (JOR Spine, 2023)
Abstract Background Nuclectomy, also known as nucleotomy, is a percutaneous surgical procedure performed to remove nucleus material from the center of the disc. Multiple techniques have been considered to perform a nuclectomy, however, the advantages and disadvantages of each are not well understood. Aims This in vitro biomechanical investigation on human cadaveric specimens aimed to quantitatively compare three nuclectomy techniques performed using an automated shaver, rongeurs, and laser. Material & Methods Comparisons were made in terms of mass, volume and location of material removal, changes in disc height, and stiffness. Fifteen vertebra–disc–vertebra lumbar specimens were acquired from six donors (40 ± 13 years) and split into three groups. Before and after nucleotomy axial mechanical tests were performed and T2‐weighted 9.4T MRIs were acquired for each specimen. Results When using the automated shaver and rongeurs similar volumes of disc material were removed (2.51 ± 1.10% and 2.76 ± 1.39% of the total disc volume, respectively), while considerably less material was removed using the laser (0.12 ± 0.07%). Nuclectomy using the automated shaver and rongeurs significantly reduced the toe‐region stiffness (p = 0.036), while the reduction in the linear region stiffness was significant only for the rongeurs group (p = 0.011). Post‐nuclectomy, 60% of the rongeurs group specimens showed changes in the endplate profile while 40% from the laser group showed subchondral marrow changes. Discussion From the MRIs, homogeneous cavities were seen in the center of the disc when using the automated shaver. When using rongeurs, material was removed non‐homogeneously both from the nucleus and annulus regions. Laser ablation formed small and localized cavities suggesting that the technique is not suitable to remove large volumes of material unless it is developed and optimized for this application. Conclusion The results demonstrate that both rongeurs and automated shavers can be used to remove large volumes of NP material but the reduced risk of collateral damage to surrounding tissues suggests that the automated shaver may be more suitable.